Long-term outcomes of triple-site versus dual-site cardiac resynchronization therapy using temporary pacing to guide individualized implantation - Michio Ogano, MD, PhD; Yu-ki Iwasaki, MD, PhD; Jun Tanabe, MD; Wataru Shimizu, MD, PhD, FHRS; Kuniya Asai, MD, PhD (Heart Rhythm O2)
Background: Cardiac resynchronization therapy (CRT) is an effective treatment for chronic heart failure, but dual-site (2V) pacing may not fully eliminate electrical dyssynchrony. Triple-site (3V) pacing, adding an additional left ventricle (LV) pacing site, may enhance CRT outcomes. Objective: This study examines the long-term effects of 2V vs 3V CRT, using temporary pacing to individualize lead placement. Methods: From 2010 to 2016, 92 patients with New York Heart Association (NYHA class II-IV heart failure, left ventricular ejection fraction (LVEF) < 35%, and QRS duration > 120 ms received CRT guided by temporary pacing. Patients underwent invasive pacing studies to measure electrical and hemodynamic improvements between 2V and 3V configurations. Based on QRS narrowing and LV dP/dtmax improvements, 27 patients were assigned to the 3V group and 65 to the 2V group. Clinical outcomes, including the clinical composite score (CCS), NYHA class, QRS duration, heart failure (HF) events, and mortality, were followed up over an average 8.3 years. Results: At 1 year, the 3V group had significantly better CCS outcomes compared with the 2V group (P = .018). Long-term follow-up showed a significantly lower HF event rate in the 3V group (P = .002), although overall mortality did not differ. Multivariate analysis identified 3V pacing as an independent predictor of reduced HF events (hazard ratio [HR] = 0.275; P = .018). Despite shorter battery life in the 3V group, device replacement rates were similar. Conclusion: Temporary pacing-guided 3V CRT provides significant long-term benefits over 2V CRT by reducing HF events. These findings support the necessity of individualized assessment and approach to eliminate electrical dyssynchrony when considering multi-site pacing CRT.